2017
DOI: 10.5811/westjem.2017.3.32853
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Pain Management Following Implementation of a Geriatric Hip Fracture Program

Abstract: IntroductionOver 300,000 patients in the United States sustain low-trauma fragility hip fractures annually. Multidisciplinary geriatric fracture programs (GFP) including early, multimodal pain management reduce morbidity and mortality. Our overall goal was to determine the effects of a GFP on the emergency department (ED) pain management of geriatric fragility hip fractures.MethodsWe performed a retrospective study including patients age ≥65 years with fragility hip fractures two years before and two years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…A study done in USA on geriatric hip fracture patients showed that patients who received fascia iliac compartment block (6% vs 60% ) in the ED had a shorter time to first analgesic use (93 minutes VS 103 minutes) and received fewer morphine equivalents in the first 24 hours [17]. In addition, a study done by Beaudoin and his colleagues showed that there is a significant decrease in pain intensity with regional nerve blocks in ED and decreased amount of rescue analgesia [18].…”
Section: Introductionmentioning
confidence: 99%
“…A study done in USA on geriatric hip fracture patients showed that patients who received fascia iliac compartment block (6% vs 60% ) in the ED had a shorter time to first analgesic use (93 minutes VS 103 minutes) and received fewer morphine equivalents in the first 24 hours [17]. In addition, a study done by Beaudoin and his colleagues showed that there is a significant decrease in pain intensity with regional nerve blocks in ED and decreased amount of rescue analgesia [18].…”
Section: Introductionmentioning
confidence: 99%
“… 26 The effect of a multidisciplinary perioperative care bundle that standardized management in the emergency department, operating theater, and ward has been shown to produce a clinically and statistically significant reduction in the incidence of delirium following hip fracture surgery, and this program included regular education for staff as well as continuous auditing of compliance. 27 , 28 Postoperative outcomes in patients may also benefit from a multidisciplinary rehabilitation model adapted to the patient with dementia, and by redefining results of rehabilitation for these patients. 29 Systematic reviews have shown that the Fracture Liaison Service (FLS) model of care is associated with significant improvement in rates of bone mineral density testing, initiation of osteoporosis treatment, and adherence with treatment for individuals who sustain fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently prescribed as an analgesic and antipyretic in the treatment of headache, toothache, migraine, dysmenorrhea, myalgia, neuralgia, musculoskeletal, tonsillectomy pain, the common cold, influenza, and other bacterial and viral infections. It can also be used as a pain controller for numerous cases in neurosurgery and emergency departments, including posterior lumbar laminectomy ( 24 ), vertebral compression fractures ( 25 ), spinal primary and metastatic tumors ( 26 ), post-craniotomy in intracranial pathology surgery ( 27 ), traumatic fractures of bones ( 28 ), urinary colic ( 29 ) and acute appendicitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%